Sodium risedronate-loaded poly(ε-caprolactone) nanoparticles: Development, physicochemical characterization, and in vitro drug release study - Gomes, Felipe Pereira; Cruz, Letícia; Ferreira, Luana Mota (Saúde (Santa Maria), 2022)
Population in all over the world is affected by bone diseases, such as osteoporosis and loss bone tissue. Sodium risedronate (Na-Ris) is one of the most used drugs to its treatment. However, it has low oral bioavailability and exhibits many side effects. In order to overcome these limitations, the search for new dosage forms is necessary. One of these alternatives is the development of nanoparticles, which are able to transport the drug to its target directly, promoting maximization of the therapeutic efficiency and minimization of the toxicity. Due to its great versatility, these systems can be applied to an assorted administration routes, such as oral, pulmonary, intravenous, among others. Thus, the objective of this study was to develop and characterize Na-Ris-loaded nanoparticles, as well as determine the drug release profile. Methods: Nanoparticles were prepared by solvent emulsification/evaporation method and characterized by mean size, polydispersity index, zeta potential, granulometric distribution, drug content and encapsulation efficiency. Afterwards, in vitro drug release was performed using the dialysis bag technique as well as the release kinetics were also studied. Results: The developed system has shown mean size of 193 ± 14 nm and polydispersity index around 0.2. Zeta potential was -9.76 ± 0,52 mV and slightly acid values for pH. The granulometric distribution demonstrated nanoparticles with a narrow size distribution and the absence of particles in the micrometer range. Regarding the in vitro release, the drug was released completely from the system in 240 minutes and the release kinetics has follow the zero-order equation. Final considerations: Thus, a nanocarrier containing a water-soluble drug was successfully developed, presenting adequate physicochemical characteristics, which can be promising for biological evaluations.